German "Universal Banking" as a Model for US Banking Reform - Jan A. Kregel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
The German 'Universal Bank' Form has frequently suggested as a model for the reform of U.S. Banking system because it does not restrict banks by means of market segmentation of their activities. This paper looks at the historical evolution of financial institutions in Germany and its modern structure. It concludes that the success of the German financial system is less due to the fact that German banks can operate in all financial markets than the unique financial supervisory structure which controls banks balance sheets, and the structure of financial asset holdings in Germany, which is primarily due to impact of the second world war. The paper concludes with a series of recommendations which would have to be implemented if the US system were to introduce all the factors which characterise the German financial system, in addition to the absence of market segmentation.
Keywords: 330